A LEGAL ANALYSIS ON FOOD SECURITY UNDER INTERNATIONAL ENVIRONMENTAL LAW - Amalia Zuhra (Faculty of Law, Universitas Diponegoro, 2014)
Food security is a global issue and a concern of the international community . Food security is related to many aspects, such as economic, social , cultural , and environmental . Linkages with food security and environmental sustainability are closely inseparable . Balanced environment will help achieve sustainable food security . On the other hand , efforts to achieve food security must be environmentally sustainable . International environmental law governing food security in several instruments both